2022
DOI: 10.1038/s41526-022-00234-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of nanoparticle dispersions unravelled by size-dependent non-occupied sites free energy versus adsorption kinetics

Abstract: The surface tension of dispersions presents many types of behaviours. Although some models, based on classical surface thermodynamics, allow partial interpretation, fundamental understanding is still lacking. This work develops a single analytical physics-based formulation experimentally validated for the surface tension of various pure nanoparticle dispersions, explaining the underlying mechanisms. Against common belief, surface tension increase of dispersions appears not to occur at low but rather at interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…It can also be affirmed that the chemisorption is reversible in the BCCPH-Cd system since the Langmuir model assumes several important aspects: the surface is homogeneous, the system is saturated, the adsorption is reversible, the adsorption heat is independent of the degree of surface coverage, and all the sites are equivalent. 82 , 83 …”
Section: Resultsmentioning
confidence: 99%
“…It can also be affirmed that the chemisorption is reversible in the BCCPH-Cd system since the Langmuir model assumes several important aspects: the surface is homogeneous, the system is saturated, the adsorption is reversible, the adsorption heat is independent of the degree of surface coverage, and all the sites are equivalent. 82 , 83 …”
Section: Resultsmentioning
confidence: 99%
“…Similar to viscosity, the measured surface tension values changed insignificantly after the addition of 1 wt% nanosilver particles before and after amidation. In general, the mechanism of surface tension in dispersions composed of nanomaterials is a complex phenomenon that depends on several parameters such as particle size and geometry, particle surface coverage, base fluid, and the mass fraction of nanoparticles at the fluid/gas interface [ 60 ]. Experimental studies published in the literature have shown contradictory trends in surface tension as a function of nanoparticle content.…”
Section: Resultsmentioning
confidence: 99%